2013
DOI: 10.1371/journal.pone.0082396
|View full text |Cite|
|
Sign up to set email alerts
|

Myelopoietic Efficacy of Orlistat in Murine Hosts Bearing T Cell Lymphoma: Implication in Macrophage Differentiation and Activation

Abstract: Orlistat, an inhibitor of fatty acid synthase (FASN), acts as an antitumor agent by blocking de novo fatty acid synthesis of tumor cells. Although, myelopoiesis also depends on de novo fatty acid synthesis, the effect of orlistat on differentiation of macrophages, which play a central role in host’s antitumor defence, remains unexplored in a tumor-bearing host. Therefore, the present investigation was undertaken to examine the effect of orlistat administration on macrophage differentiation in a T cell lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…FASN is considered an oncogene in carcinogenesis and has emerged as a potential therapeutic target for lymphoma ( 37 , 38 ). In the present study, substantial evidence is presented regarding the association of FASN expression with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…FASN is considered an oncogene in carcinogenesis and has emerged as a potential therapeutic target for lymphoma ( 37 , 38 ). In the present study, substantial evidence is presented regarding the association of FASN expression with DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…As for another group of GO terms, there are multiple immune responses associated GO terms, including positive regulation of macrophage differentiation and cellular response to interferon-alpha. According to recent publications, macrophage differentiation ( Kant et al, 2013 ; Arlt et al, 2020 ) and interferon-alpha ( Hermine et al, 2002 ) associated immune responses have both been reported to be associated with the pathogenesis of lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of FASN in cancer cells has staid acquaintances with the regulation of antitumor immune response. The elevated level of FASN, observed in T-cell tumors, correlated with the decreased level of antitumor response by tumor-infiltrating macrophages ( 184 ). Moreover, inhibition of FASN through small molecule inhibitors withdraws the suppression of hematopoietic differentiation of bone marrow cells ( 184 ).…”
Section: Immunosuppression and Immune Escapementioning
confidence: 99%